EXAMINING THE EFFECTS OF SOCIAL MEDIA ON ADOLESCENT IDENTITY FORMATION AND MENTAL HEALTH - Amna Khan (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Social media has become an integral part of modern adolescence, shaping identity formation and influencing mental health outcomes. This study investigates the impact of social media usage on adolescents’ psychological well-being, self-perception, and identity development. It explores both positive and negative effects, with a focus on social comparison, self-esteem, and the risk of mental health issues like anxiety and depression. The findings provide insight into how adolescents use social media as a tool for social interaction and identity exploration, while also acknowledging the challenges it poses. This paper presents strategies to mitigate the negative consequences of social media usage on adolescent mental health.